Impacts of Crime on Socio-Economic Development - Jonathan, Okpuvwie Ejuvweyere; Olusola, Akinyede Joseph; Bernadin, Tohozin Coovi Aime; Inoussa, Toko Mouhamadou (Mediterranean Journal of Social Sciences, 2021)
Crime is as old as man and it exists in every society in respective of its level of development. The rate at which criminals operate unhindered in most societies especially in developing countries around the world is worrisome. Crime creates fear and untold suffering among people. Crime often stands as a barrier to socio-economic growth of society, discourages investment, increases the cost of transactions and ultimately fuel migration which eventually creates economic development disparities around the world. The aim of this study is to analyze the manifestation of crime the world over with a view to intimating government of all countries to have a firm control of all criminal activities in their respective countries for a better society. The approach methodology is based on a literature review of scientific journals and reports. Secondary data were sourced from both published and unpublished works as the study applies descriptive method. The main results showed various manifestations of crimes such as banditry, kidnapping, rape, stealing and murder among others. Therefore, crime fuels corruption and destabilizes development of any society.  In conclusion, crime knows no boundary nor personality as it affects people at all levels. This sad activity will continue to be a major factor of lack of socio-economic development if no strong action is taken by governments to effectively tackle the activities of criminals, terrorists and bandits around the world.   Received: 14 May 2021 / Accepted: 5 August 2021 / Published: 5 September 2021